Working Time Accounts and Turnover - Andrey Launov (Institute of Labor Economics (IZA), 2017)
Working time account is an organization tool that allows firms smoothing their demand for hours employed. Descriptive literature suggests that working time accounts reduce turnover and inhibit increase in unemployment during recessions. In a model of optimal choice of hours by a firm I show that working time account does not necessarily guarantee lower turnover. Turnover may be reduced or increased depending on whether a firm meets economic downturn with surplus or deficit of hours and on how productive this firm is. The model predicts that working time accounts contributed positively to reducing turnover in Germany during the Great Recession.
Keywords: J23; J63; 330; labour demand; working hours; working time accounts; turnover; Great Recession; Germany